Financial Aspects of Waste Collection and Management in Poland Using KAP Method (Knowledge, Attitudes, Perception) - Kamila Adamowicz (Communications of International Proceedings, 2022)
Vigorous growth in consumption all over the world, leads to the generation of increasing amounts of both: industrial and municipal waste. This causes many problems and challenges. To prevent the excessive generation of waste, its rational use and safe disposal is one of the most important challenges faced by modern cities. Since waste management and waste management policy are of broad interest to the European Union, both in terms of legal solutions and those protecting the natural environment and economic use of waste, Poland also follows these trends, adjusting its legislation to the EU legislation. Youth is a key group that has a real impact on changes related to the financing of the waste collection and management economy. Good understanding of the topic, knowledge, perception builds a strong attitude aimed at supporting waste management, for example through environmental education. In order to check the aspects related to knowledge, attitude and perception, a questionnaire using the KAP method was conducted. In the study the response rate was 78% out of 150 students.
Keywords: waste management; public finances; public expenditure; public revenue; European Union